Göncz, L. (2021). The psychology of multilingualism: Concepts, theories and application. Cambridge Scholars Publishing - Ghanmi, Rabeb (Lesya Ukrainka Eastern European National University, 2024)
This review critiques The Psychology of Multilingualism: Concepts, Theories and Application by Lajos Göncz whose research contributed extensively to the field of psychology of bilingualism and minority studies. In light of the quintessential body of research investigating bilingualism and multilingualism as intriguing complex phenomena, this book provides a comprehensive multidisciplinary approach to the research of bi- and multilingualism. Göncz approaches bi-/multilingualism as a cognitively challenging experience from a psychological, individual, and societal perspective. Basic concepts, theories, and definitions related to the psychological regularities of multilingualism are discussed in the book. Göncz also explores bi-/multilingualism from the perspective of developmental and personality psychology, elucidating the effect of speaking multiple languages on emotions, behavior, and cognitive development. Additionally, issues pertaining to the social psychology of multilingualism, including biculturalism, multiculturalism, and cultural diversity, are scrutinized, offering insights into the importance of preserving minority languages and cultures. The book also touches upon the educational aspects of the psychology of multilingualism, revisiting models of bi-/multilingual education that might be implemented to stimulate language development in the dominant as well as in the minority language.
Keywords: bilingual and multilingual education; advantages of bilingualism and multilingualism; bi- and multiculturalism